EMU and Long Interest Rates in Germany - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper, 1996)
The presence of an 'EMU premium' in German long rates is tested by examining the co-movement of German and other European yields, as well as the exchange rate of the private ECU, in reaction to EMU-related events. If German yields incorporate an 'EMU premium' while other European currencies expect lower interest rates from EMU, then German and other European long yields should react in opposite directions to events affecting the probability of EMU. In fact, they typically react in the same direction. Similarly, events which lead to an appreciation of the private ECU are associated with a decline in German yields.